2020
DOI: 10.3892/ol.2020.12251
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced circular RNA hsa_circ_0008450 accelerates hepatocellular cancer progression via the miR-431/AKAP1 axis

Abstract: Hypoxia facilitates the progression of numerous cancers. Circular RNAs (circRNA) have been revealed to be involved in the process of tumors mediated by hypoxia. However, the role and molecular mechanism of circular RNA hsa_circ_0008450 (circ_0008450) in hepatocellular cancer (HCC) under hypoxic conditions has been rarely reported. Expression levels of circ_0008450, microRNA(miR)-431 and A-kinase anchor protein 1 (AKAP1) were examined using reverse transcription-quantitative PCR. Cell viability, apoptosis and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Circ_0061140 has been reported as an oncogene in serval human cancers, such as prostate cancer [ 11 ], bladder cancer [ 10 ], endometrial cancer [ 27 ]. In addition, intratumoral hypoxia has been identified as a driving force of tumor progression [ 28 , 29 ], and circRNA could be regulated by hypoxia in tumors [ 30 , 31 ]. In this work, we identified that circ_0061140 level was alerted by hypoxia stimulation, suggesting that circ_0061140 might act as a crucial function in LAUD development under hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Circ_0061140 has been reported as an oncogene in serval human cancers, such as prostate cancer [ 11 ], bladder cancer [ 10 ], endometrial cancer [ 27 ]. In addition, intratumoral hypoxia has been identified as a driving force of tumor progression [ 28 , 29 ], and circRNA could be regulated by hypoxia in tumors [ 30 , 31 ]. In this work, we identified that circ_0061140 level was alerted by hypoxia stimulation, suggesting that circ_0061140 might act as a crucial function in LAUD development under hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, hypoxia-elevated circRNF20 acts as a miR-487a sponge to upregulate the transcription and protein levels of HIF1α, thus promoting the glycolysis and tumorigenesis of BC [26]. Under hypoxia, circ_0008450 facilitates hepatocellular cancer progression by targeting the miR-431/A-kinase anchor protein 1 (AKAP1) axis [27]. Hypoxia-induced ebv-circLMP2A up-regulates HIF1α by interacting with KH-type splicing regulatory protein (KHSRP), leading to angiogenesis of Epstein-Barr virus-associated gastric carcinoma [28].…”
Section: Discussionmentioning
confidence: 99%
“…The circ-0051443 from circulating exosomes or HCC tissues regulated BAK1 expression by combining with mir-331-3p to promote cell apoptosis or cell cycle arrest in HCC, and inhibit the biological behavior of HCC cells in vivo or nude mice HCC xenografts[ 100 ]. Another interesting study also showed that has_circ_0008450 expression in HCC tissues or cells might inhibit HCC progression by regulating the mir-214-3p/ezh2 axis[ 101 , 102 ]. These data suggested that specific ncRNAs were useful molecular targets for HCC therapy.…”
Section: Synergy Of Non-coding Rnasmentioning
confidence: 99%